Chitinase 3‐like‐1 promotes intrahepatic activation of coagulation through induction of tissue factor in mice. Issue 6 (June 2018) - Shan, Zhao; Liu, Xiaodong; Chen, Yuan; Wang, Meng; Gao, Yue Rachel; Xu, Liangguo; Dar, Wasim A.; Lee, Chun Geun; Elias, Jack Angel; Castillo, Pavel Davizon; Paola, Jorge Di; Ju, Cynthia
Abstract : Coagulation is a critical component in the progression of liver disease. Identification of key molecules involved in the intrahepatic activation of coagulation (IAOC) will be instrumental in the development of effective therapies against liver disease. Using a mouse model of concanavalin A (ConA)‐induced hepatitis, in which IAOC plays an essential role in causing liver injury, we uncovered a procoagulant function of chitinase 3‐like 1 (Chi3l1). Chi3l1 expression is dramatically elevated after ConA challenge, which is dependent on ConA‐induced T cell activation and the resulting interferon γ and tumor necrosis factor α productions. Compared with wild‐type mice, Chi3l1 −/− mice show less IAOC, reduced tissue factor (TF) expression, and attenuated liver injury. Reconstituting Chi3l1 −/− mice with recombinant TF triggers IAOC and augments liver injury. Conclusion: Our data demonstrate that Chi3l1, through induction of TF via mitogen‐activated protein kinase activation, promotes IAOC and tissue injury. (Hepatology 2018;67:2384‐2396).